2009
DOI: 10.1080/10503300902914147
|View full text |Cite
|
Sign up to set email alerts
|

Structural change as a predictor of long-term follow-up outcome

Abstract: Based on data from psychoanalytic long-term psychotherapies, the predictive value of three measures of pre-post change for retrospective patient assessments of outcome at 1-year and 3-year follow-up was investigated. Pre-post changes were measured using the Global Severity Index (GSI), the Inventory of Interpersonal Problems (IIP) total score, and the Heidelberg Structural Change Scale (HSCS). In line with psychoanalytic theory, it was assumed that structural changes cause especially persistent changes and wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
1
26
0
7
Order By: Relevance
“…Grande et al [47] and Rudolf et al [48] have shown that in outpatients undergoing psychodynamic or analytic psychotherapy, a higher level of restructuring on the HSCS also corresponded with fewer symptoms at the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Grande et al [47] and Rudolf et al [48] have shown that in outpatients undergoing psychodynamic or analytic psychotherapy, a higher level of restructuring on the HSCS also corresponded with fewer symptoms at the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As modalidades de psicoterapia avaliadas foram: psicoterapia psicodinâmica -PP (Lilliengren et al, 2015;Berghout e Zevalkink, 2009); psicoterapia psicodinâmica de curto prazo -PPCP (Leichsenring et al, 2014;Amianto et al, 2011); psicoterapia psicodinâ-mica de longo prazo -PPLP (Leichsenring et al, 2014;Arvidsson et al, 2011); psicoterapia psicodinâmica intensiva e curto prazo -PPI-CP (Solbakken e Abbass, 2015); psicoterapia psicodinâmica intensiva -PPI (Abass et al, 2015); psicoterapia psicodinâmica de apoio -PPA (Driessen et al, 2013); psicoterapia psicodinâmica breve -PPB (Amianto et al, 2011); psicoterapia psicodinâmica focal -PPF (Zipfel et al, 2014); tratamento comunitário de foco psicodinâmico -TCFP (Vinnars et al, 2009); psicoterapia psicodinâmica interpessoal -PIT (Sattel et al, 2012); psicoterapia psicodinâmica pela internet -PPIN (Johansson et al, 2013); psicanálise -PA (Grande et al, 2009); psicaná-lise com predomínio de interpretações transferências -PAT e sem interpretações transferenciais -PAST (Høglend et al, 2008) e terapia cognitivo comportamental -TCC; (Levi et al, 2015;Zipfel et al, 2014); terapia cognitivo comportamental pela internet -TCCI (Johansson et al, 2013); terapia do esquema -TE (Gude e Hoffart., 2008); terapia de apoio -TA (Vinnars et al, 2009); e, terapia focal -TF (Heinonen et al, 2012). Foram encontradas também intervenções com medicamentos como a fluoxetina (Sørensen et al, 2011), sozinhos ou combinados com psicoterapia psicodinâmica (Koppers et al, 2011); e também intervenções combinadas com outros tratamentos multidisciplinares, tais como dieta alimentar e acompanhamento familiar (Abba-te Daga et al, 2015).…”
Section: Modalidades De Psicoterapiaunclassified
“…Outro método utilizado para complementar os questionários foram entrevistas presenciais semiestruturadas desenvolvidas para o próprio estudo, ou entrevistas estruturadas, por exemplo: Operationalized Psychodynamic Diagnosis -OPD Task Force (Levi et al,2015;Vinnars et al, 2009;Marttunen et al, 2008;Johansson et al, 2013;Kronström et al, 2009;Koppers et al, 2011;Høglend et al, 2008;Gude e Hoffart, 2008;Abbate-Daga et al, 2015;Berghout e Zevalkink, 2009;Lilliengren et al, 2015;Grande et al, 2009;Arvidson et al, 2011;Leichsenring et al, 2014). O estudo que avaliou custo-efetividade dos serviços de saúde também utilizou, além dos questionários, os registros nacionais de verificação para compor as medidas de follow-up (Abass et al, 2015).…”
Section: Métodos E Medidas Utilizados No Follow-upunclassified
See 1 more Smart Citation
“…Psychodynamische Therapie impliziert, dass sich bezüg-lich des psychodynamischen Fokus etwas verändern muss, damit Symptombesserung eintreten kann. Im Prä-Post-Verlauf wurden schwache Korrelationen zwischen der Veränderung der HUS und globaler Symptombelastung berichtet (Grande et al , 2009Schneider et al 2006). Ob dieser Aspekt auch für die Ressourcenrealisierung bedeutsam ist, wurde bisher nicht untersucht.…”
Section: Introductionunclassified